Prevalence and factors associated with suicidal ideation among university students (2003)
Objectives: To quantify the prevalence of suicidal ideation in a population of university students, to characterize groups in connection with ideation and suicidal behavior, and to determine the variables associated with suicidal ideation and suicide attempts. Methods: Observational, analytic and cross-sectional study of a probabilistic sample of the population studied. An instrument for measuring suicide risk and associated variables was applied to this sample. Results: The prevalence of the current suicidal ideation was 3,6 %, and 18 % in the last year. Both suicidal ideation and history of suicide attempts were higher among female students. Rape history, being alone more than eight hours a day, and female gender were the factors more strongly related to suicidal ideation. A relationship suicidal ideation and awareness of the suicide of others was not found in this sample. Conclusion: A history of rape, remaining alone for more than eight hours during the day, and being a woman should alert the clinician about the possibility of suicidal ideation. It is recommended to explore and assess suicidal ideation in all people with these factors.